A Development toward Matching Pursuit Algorithm Aims To Reduce Calculation Mass in the Process of the Compessed Sampling and Errors in the Signal Recovery Process - Tran, Vu Kien; Nguyen, Ngoc Minh; Nguyen, Le Cuong (Old Journal, 2017)
Many works related to the signal restoration from discrete samples that are unsatisfactory requirements of Nyquist's criteria has been deployed and published recently. There were many algorithms to solve this issue, such as CoSaMP and the matching pursuit. This article presents a developed algorithm which is based on the matching pursuit algorithm to recover multi-dimensional architectures. This development is permissible to reduce the calculation mass in several cases along with a number of dedicated conditions when sampling signal compression. Simultaneously, the article will demonstrate this algorithm also makes reduce the occurred error at each step in the signal recovery process by using the mathematical method.